2021
DOI: 10.1038/s41467-021-26153-7
|View full text |Cite
|
Sign up to set email alerts
|

Pig genome functional annotation enhances the biological interpretation of complex traits and human disease

Abstract: The functional annotation of livestock genomes is crucial for understanding the molecular mechanisms that underpin complex traits of economic importance, adaptive evolution and comparative genomics. Here, we provide the most comprehensive catalogue to date of regulatory elements in the pig (Sus scrofa) by integrating 223 epigenomic and transcriptomic data sets, representing 14 biologically important tissues. We systematically describe the dynamic epigenetic landscape across tissues by functionally annotating 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
129
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(148 citation statements)
references
References 91 publications
(112 reference statements)
16
129
0
3
Order By: Relevance
“…Previous studies have provided powerful evidence for the crucial roles of cis‐regulatory elements (CREs) in identifying causative variants of complex traits 16,72,73 . With driven efforts by FAANG, a growing body of studies engaged in the functional annotation of farm animal genome have emerged, further leading to characterize the genetic architecture of important economic traits and enhance the animal performance 20,22,74,75 . Although major advances have been made in bovine epigenome study, the epigenetic basis for foetal skeletal muscle development remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have provided powerful evidence for the crucial roles of cis‐regulatory elements (CREs) in identifying causative variants of complex traits 16,72,73 . With driven efforts by FAANG, a growing body of studies engaged in the functional annotation of farm animal genome have emerged, further leading to characterize the genetic architecture of important economic traits and enhance the animal performance 20,22,74,75 . Although major advances have been made in bovine epigenome study, the epigenetic basis for foetal skeletal muscle development remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we further investigated the enrichment of SINE families in 15 distinct chromatin states across 14 tissues ( Fig. 2d , Supplementary Information) 68 . We observed that young SINE groups (youngest and younger) show lower enrichment in most of the functional chromatin states than old SINE groups (older and oldest), and the enrichment degree of SINE in chromatin states was roughly similar across 14 tissues.…”
Section: Resultsmentioning
confidence: 99%
“…These data provided information about the regulatory element status of the region based on enrichment of histone marks (H3K27me3, H3K4me1, H3K27ac, H3K4me3), ATAC-Seq and CTCF data in 15 tissues of two male Bos taurus . The method to classify the genomic region regarding the regulatory element state was described by Pan et al [ 70 ]. In summary, the epigenetic marks data described above were used to train a chromatin state prediction model in ChromHMM69 (v.1.20) and 15 states were chosen.…”
Section: Methodsmentioning
confidence: 99%